Medierede erindringer på tværs af generationer. Fokus på metode - Grønning, Anette (Aktualitet - Litteratur, kultur og medier, 2021)
This article is about one of many methods of collecting, analyzing and disseminating statements and descriptions of media memories across generations. The starting point is an experimental data collection consisting of long-term digital inbox conversations with two family chains: one comprising son, father, and paternal grandfather, and one comprising daughter, mother, and maternal grandmother. The youngest family members represent a ‘here-and-now’ presentism culture, while the middle and eldest family members represent a more classic ‘what has taken place’ culture. The study focuses on the importance of experimental data collection and documents that digital media today play a central role in research into memories.